Effects of wearing different facial masks on respiratory symptoms, oxygen saturation, and functional capacity during six-minute walk test in healthy subjects. - Sauwaluk Dacha; Busaba Chuatrakoon; Kanphajee Sornkaew; Kamonchanok Sutthakhun; Putsamon Weeranorapanich (Canadian Journal of Respiratory Therapy, 2022)
Background: During the current COVID-19 pandemic and increased air pollution levels, wearing a facial mask has been recommended. This study aimed to compare the impact of wearing different masks when performing a submaximal functional activity (six-minute walk test; 6MWT) on respiratory symptoms, oxygen saturation, and functional capacity. Methods: Twenty-nine subjects (10 men, 19 women; age 22 ± 1 yr.; FEV1/FVC 0.90 ± 0.01) performed four rounds of 6MWT wearing different masks (surgical (Medima SK, Thailand), handmade cloth, and N95 (3M AuraTM 1870+, USA)) and while not wearing a mask. Respiratory symptoms (dyspnea and breathing effort), oxygen saturation, and other physiological parameters were assessed before and after each walking trial. Results: Six-minute walking distances were comparable between walking trials (P = 0.59). At the end of minute 6, a significant difference between groups was found on dyspnea (P = 0.02) and breathing effort (P < 0.001). Post hoc tests showed that wearing a cloth mask significantly increased dyspnea (P = 0.004) compared to wearing a surgical mask. Wearing a cloth mask also significantly increased breathing effort compared to wearing a surgical mask (P < 0.001) and not wearing a mask (P < 0.001). Likewise, while wearing an N95 mask, breathing effort significantly increased compared to wearing a surgical mask (P = 0.007) and not wearing a mask (P = 0.002). Conclusions: Wearing different masks while performing submaximal functional activity results in no differences in functional performance, oxygen saturation, heart rate, or blood pressure. However, wearing cloth masks and N95 masks results in higher respiratory symptoms.